(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Soil water characteristic curve (SWCC) is very important in the study of unsaturated soil because it represents a soil’s ability to store and release water as it is subjected to various soil suctions. This storage of moisture in soil is paramount in irrigation engineering, as it determines the irrigation scheduling in dryland. This study reviews some SWCC model’s performance to predict the soil from some selected soils in Nigeria from previous work. This previous work contains 7 points between 0 – 1,500 kPa. Seki, which is bimodal, tends to perform better than the rest with R2 value of 0.99. Generally, the bimodal models performed better than the unimodal, due to the flexibility of the curve. However, with the removal of the reference point of 1,000,000kPa (leaving 7 points), all the unimodal models had good performance in the topsoil. Fredlund and Xing performed best and van Genuchten performed poorly in the subsoil. Also, it was observed with the increase in both the organic matter contents and electrical conductivity, the performance of the models decreased. From this review, it is observable that in analysis of 8 or more points and 3 to 7 points Seki’s model and Fredlund and Xing model can be used respectively for further research in the study of dryland soils of Nigeria